The role of the Shura in resolving disputes between the Iraqi state and the Kurdistan Region - األستاذ المساعد امدکجور َاشه ودىد أوٌي سنٌىان (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Islam has dealt with the problems and dilemmas that are best represented by the Shura, a poll of the majority of the Ummah, or on behalf of it, with the aim of reaching the closest opinion to the right and the right of the Shari'a, in preparation for taking the appropriate decision. Not every matter is subject to Shura. The issues and dilemmas related to the future of the nation or the state in which it is not written are matters of judgment. They are subject to shura, and not to the practice of shura in a specific form. It is sometimes practiced by consulting the followers in the nation, sometimes by presenting the matter to the people to know its opinion and sometimes by establishing a shura council.